The trivialization of women's football in Turkey - Nuhrat, Y. (Oxford University Press, 2023)
Football is considered mainly a men's sport and pastime in Turkey, much like around the world, resulting in unequal treatment towards female practitioners. Women are othered through football, one manifestation of which is the trivialization of sport when played by women. This chapter addresses the trivialization of women's football in Turkey on multiple levels, from mundane procedures on match days to larger scale labor exploitation tied to lack of professionalization. I demonstrate that the multiple hierarchies within which Turkey's female footballers are situated make this a field of insecurity and precarity for them, limiting their resources for mobilization or resistance. The chapter is based on four months of qualitative fieldwork, mostly in Istanbul, with a total of 38 participants including footballers, coaches, club and federation administrators, sponsors, media representatives, and academics. © Abdullah Al-Arian, 2022. All rights reserved.
Keywords: Football; Gender İnequality; Labor Exploitation; Turkey; Women